PERANCANGAN SISTEM INFORMASI KELENGKAPAN REKAM MEDIS RAWAT JALAN MENGGUNAKAN VISUAL STUDIO DI RSKGM - Rifdi Salawati; Erix Gunawan; Cahyadi Agustin (POLITEKNIK PIKSI GANESHA, 2022)
This research aimed to identify the analysis of information system of the completeness medical record by using Microsoft Visual Studio at Dental and Oral Specialist Hospital. The research method uses qualitative methods with a descriptive approach. Data collection techniques used direct observation, online observation, and literature study. Method using Waterfall Model (Waterfall). Based on the author’s observation during this research problems which are found: (1) The completeness of analysis medical record of the hospitalization patient is not yet entirely computerized. (2) Incomplete medical records are still found. (3) Overdue the refund of medical record from a maintenance room into the medical record processing. As for suggestions to overcome problems in the complete system of road medical record at the Special Dental and Oral Hospital, namely: (1) it is necessary to integrated system and to effective more. (2) It is necessary to make the strict rules for officials negligent in the filling of medical record and also for the officer who are late to submit the inpatient medical record data processing to the medical record division. Keyword: Information System, completeness, Visual Studio